Malaysia : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Observance of Core Principles for Effective Deposit Insurance Systems. (IMF Staff Country Reports; Country Report ;, 2013)
This paper evaluates and addresses Malaysia's compliance with the Core Principles for Effective Deposit Insurance Systems (Core Principles), and reviews relevant laws, regulations and regulatory and supervisory practices related to conventional banking sector, and the operations of Perbadanan Insurans Deposit Malaysia (PIDM). Though several weaknesses in the legal framework have been noted in this assessment, there has been no experience with bank failures in Malaysia since PIDM's establishment in 2005. The paper also covers Islamic deposits, which manage a separate Islamic Deposit Insurance Fund (IDIF).